GENDER DIVERSITY AS THE MODERATING FACTOR IN THE INFLUENCE OF FINANCIAL FACTORS ON THE FIRM VALUE: A STUDY ON COMPANIES LISTED IN KOMPAS 100 INDEX in 2015‐2019 - Sri Sumira; Wiwiek Prihandini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to analyze the influence of financial factors on firm value with gender diversity as the moderating variable. Male directors tend to show risk-takers traits, whereas women directors are more risk-averse which become effective in decision-making. Gender diversity is proxied by the presence of women on the board of directors and on the board of commissioners. The samples are companies admitted in Kompas 100 index and listed on IDX from 2015 to 2019. Firm value was measured by using the Tobin's Q formula. The data were processed using Eviews 11. To determine the model for the hypothesis testing, the Chow test and Hausman test were carried out, and fixed effect model was selected. This study proves that the presence of women can weaken the relationship between profitability and firm value, and it can strengthen the relationship between activity ratio and firm value. However, the presence of women cannot strengthen or weaken the influence of leverage and liquidity on firm value. It is recommended that a company has women representation in the structure of the board because women directors have more sensitivity to risk which can compensate the character of male directors who are risk-takers. Keywords: firm value, profitability, leverage, current ratio, activity ratio, gender diversity, companies in Kompas 100 index